Long-Term Neurological Sequelae and Disease Burden of Japanese Encephalitis in Gansu Province, China. Issue 1 (21st October 2021) - Wang, Xuxia; Su, Li; Sun, Shougang; Hu, Wenbiao; Mu, Qiuling; Liang, Xuefeng; Jin, Na; Dai, Tian; Li, Hui; Zhuang, Guihua
Background and objects: The study aimed to evaluate the long-term neurological sequelae and the disease burden of JE in Gansu, China. Methods: JE patients were included as study population from 2005–2011 in Gansu, and a follow-up survey was conducted in 2007–2014. Pair-matched healthy individuals were selected as controls. All subjects underwent a neurological examination and intelligence quotient (IQ) and memory quotient (MQ) assessments. Then, the disability-adjusted life years (DALYs), and direct and indirect medical expenses were systematic assessed. Results: Forty-four point seven percent of the JE patients had objective neurological deficits, compared with 2.4% of controls. Subnormal intelligence was found in 21.2% of JE subjects, compared with 1.2% control who exhibited a mildly reduced IQ. Abnormal MQ scores were noted in 56.3% JE subjects, compared with only 12.7% controls. Prevalence of each sequelae caused by JE were significantly higher in adults than in younger subjects. Furthermore, median DALY lost due to JE was 9.2 per subject. Median economic cost of JE was approximately 2776.6 per subject and significantly higher in adults than in younger subjects. Findings and Conclusions: JE patients suffered from severe neurological sequelae and high disease burden, resulting in a significant downstream burden for both the patients (especially adults) and the healthcare system.